Türkiye'de Bölgesel Havayolu Şirketi Kurulması - Tunç, Ataç (Fen Bilimleri Enstitüsü)
İnsanoğlunun uçma arzusu ile başlayan havacılığın, tüm dünyada askeri ve haberleşme amaçlı gelişmesinin ardından, yolcu taşımacılığında da son 90 yılda sivil havacılıkta çok yol kat edilmiştir. Uçakların kapasiteleri, boyutları artmış, kıtalar arası uzun uçuşlar önem kazanmıştır. Uzun mesafeli yolculuklarda neredeyse tamamen havayolu ile taşıma tercih edilmeye başlanmıştır. Son yıllarda gerçekleştirilen uluslararası uçuşlar göz önüne alındığında, havayolu şirketlerinin taşıdığı yolcu sayılarında bir doygunluğa ulaşılmış ve yolcu sayıları genellikle sabit kalmaya başlamıştır. Buna karşın, gün geçtikçe sivil havacılık otoriteleri tarafından alınan emniyet tedbirleri arttırılmakta ve cezai yaptırımlar ağırlaştırılmaktadır. Bu durum, kar oranları düşen, hatta zarar etmeye başlayan havayolu şirketlerini yeni yolcu arayışlarına yönlendirmiştir. Böylece, çeşitli ülkelere ait havayolu şirketleri ikili anlaşmalar yaparak pazar paylaşımı yapmakta, ya da ulusal yolcu taşımacılığına yönelip bölgesel uçuşlar gerçekleştirmenin yollarını aramaktadırlar. Bu çalışmada da, Türkiye’de bölgesel havayolu şirketi kurulması ile ilgili detaylar incelenecektir. Dünyada Deregülasyon Yasası’nın kabulünün ardından, karayolu ile uzun süren, büyük havayolu uçakları ile de düşük kar getiren uçuş noktalarında bir boşluk oluşmuştur. Ayrıca sivil havacılık şirketlerinin önündeki devlet engellerinin de kaldırılması ile bu boşlukların değerlendirilmesi, bölgesel havayolu şirketlerinin sivil havacılık sahnesine girmesiyle olmuştur. Türkiye’ye baktığımızda ise, coğrafi yapısı ve geniş sınırları ile ulusal taşımacılıkta havayolu kullanımı için oldukça elverişli bir yapıya sahip olduğu görülür. Şehir merkezleri arasında konumlanan engebeli yer şekilleri karayollarını uzatmakta, yolcular havayolu kullanarak daha kısa sürede diğer şehirlere ulaşmak istemektedirler. Diğer yandan, iç kesimlerde yer alan yüksek nüfus ve Türkiye’nin yerli ve yabancı turistler için çok cazip bir noktada bulunması bölgesel havayolu şirketi kurulmasında iştah kabartan etmenlerdendir. Özellikle tatil zamanında yolcular uzun karayolu yolculukları yerine hem zamandan kazanmayı, hem de konforlu ve kaliteli bir yolculuk yapmayı tercih etmektedirler. Bunlara ek olarak, Türkiye büyüyen bir ekonomiye sahip olduğundan havayolunu kullanabilecek ekonomik güçte nüfus da yadsınamayacak kadar fazladır. Bölgesel havayolu şirketleri faaliyetleri sırasında birçok operasyon modeli kullanırlar. Çoğunlukla büyük havayolu şirketleri ile işbirliği içerisinde varlığını sürdüren bölgesel havayolu şirketleri, uçaklarını büyük havayolu şirketlerine kiralayarak, büyük havayolu şirketlerinin marka değerinden yararlanıp ayrıcalıklı satış hakkı alarak, kod paylaşımlı uçuşlar gerçekleştirerek ya da büyük havayolu şirketlerinin merkez uçuş noktalarından, onların uçuş tarifelerine uygun saatlerde bölgesel seferler düzenleyerek ticari varlıklarını devam ettirmeye çalışırlar. Bu iştiraklerin avantajlı ve dezavantajlı tarafları bu çalışma içerisinde ele alınacaktır. Çalışmanın bir diğer bölümünde Türkiye’de bir bölgesel havayolu şirketi kurulması için gereken yasal zemin incelenecektir. Yasal mevzuat çoğunlukla, SHY-6A Ticari Hava Taşıma İşletmeleri Yönetmeliği düzenlemelerini ele almaktadır. İşletme Ruhsatı alınması için gereken başvuru süreçleri, teminat bedelleri, gerekli personel istihdamının sağlanabilmesi gibi konular detaylarıyla ele alınmıştır. Yasal mevzuat şirketin operasyon koşullarının belirlenmesi hususunda da şirket kurucularına rehberlik etmektedir. Uçakların satın alınması ya da kiralanarak operasyon yapılması ile ilgili düzenlemeler ve teminat bedelleri farklılıklar içermektedir. Bu farklılıkların da ele alındığı çalışmada, tüm yasal zemin oluşturulduktan sonra, örnek olay işlenmiş ve bir havayolu şirketi kurulumunun incelenmesine geçilmiştir. Bölgesel havayolu şirketi kurulmasında atılması gereken ilk ve en önemli adım, sınır koşullarının doğru belirlenmesidir. Öncelikle yatırıma uygun pazar araştırması yapılarak başlangıçta ve daha sonrasında, dönemsel ve sürekli olarak uçulabilecek güzergahları seçmek gerekmektedir. Bu seçim beraberinde, uçuş operasyonlarının dolayısıyla şirketin ana merkezinin nerede olacağının, uçakların yolcu kapasitelerinin, inilecek meydan özelliklerine ve uçuş mesafelerine göre uçak ve motor tiplerinin belirlenmesini sağlayacaktır. Daha sonra, seçilen uçakların bakım giderlerinin belirlenmesi, mürettebatının ve bakım personelinin seçimi, ilk ve tekrarlı eğitimlerin hesaplanması bakım ve uçuş maliyetlerinin çıkarılması aşamasına geçilerek, seçilen uçakların öngörülen yolcu sayısına göre karlı bir yatırımı sağlayıp sağlayamayacağı incelenmelidir. Bu çalışmada da şirketin faaliyet noktaları, uçak tipi ve sayısı, mürettebatı, bakım personeli, yönetici personeli belirlendikten sonra kurulum maliyeti hesabı için; ruhsat bedelleri uçak kiralama bedelleri, kurulması gereken yönetim ve bilişim sistemleri, bina giderleri, personel maaşları ve ilk eğitim giderlerini içeren detaylı maliyet hesapları yapılmıştır. Buna göre yeni kurulan bir havayolu şirketinin kurulum maliyetini ne kadar sürede amorti edebileceği, üç yıllık doğrudan ve dolaylı giderler ile aynı zamanda operasyon gelirleri dahil edilerek incelenmiştir. Bunun sonucunda iç karlılık oranının ve net bugünkü değerinin ne kadar olacağı belirlenmiştir. Sonuçlar ve değerlendirme bölümünde ise, ele alınan şirketin maliyet oranlarının, literatür araştırmalarındaki değerlerle benzerlikleri gözlemlenmiş, çalışmada ele alınan yapının gerçekleştirilebilir olduğu sonucuna erişilmiştir. Tüm bunlara bakıldığında, Türkiye’nin bölgesel havayolu taşımacılığının gelişmesi için oldukça elverişli bir ortam olduğu gözlemlenmektedir.

The Global growth of the aviation for military and communicational purposes, right after the historical beginnig of aviation as a passion of mankind through the flight, is resulted as an improvement civil aviation in 90 years. The capacity, dimensions of the aircrafts and intercontinental flight demands are increased rapidly in recent century. Passengers are became addicted to the air tranportation for long distance travels. However, after this accelerated growth in the aviation market, the number of carried passengers have stayed almost stable for the last 3 years. And also, civil aviation authorities started to take stricter precautions against airlines in a manner of providing airworthiness. As a result of the stable market and unchallengeable precautions, airline companies have changed their target through the regional market day by day to protect themselves from bankrupcy or loosing profitability. After the application of Deregulation Law in aviation in early 1980’s, big airline companies started to leave unprofitable regional flight areas and they changed their flight structures from “point to point” flights to “base to point” long distance flights. This less profitable area evacuation movement, is resulted with the incorporation of regional airlines in those areas in civil aviation. In the early 2000’s, airline companies started to look for some new methods to develop market size again, by performing some cooperations with regional airlines or by promoting them. Aviation market has also reshaped according to the passenger demand on regional flights. Regarding to the geographical condition of Turkey, the mid-region of the country is covered with full of mountains. This condition results in a very important demand on air transportation. Passengers do not want to waste time and miss comfort as in long distance road trips, especially on holidays. In addition, regarding the developing economy of Turkey, there are many passengers would prefer to use airlines. Developing economy, geographical topographies and tourism potential makes Turkey more valuable localization for foundation of a regional airline service company. Regional airline companies have used many different operation models during their operations. Most of regional airlines prefer to make cooperation with leading airline companies. The common way for this cooperation is leasing the aircrafts to other airline companies. The other operation type is using their well-known brand of a leading airline in the market, by franchising and by code sharing agreements. The other cooperation method is scheduling consecutive flights. All advantages and disadvantages of these cooperation methods are mentioned widely in this study. Another section of this study would be the review of the civil aviation regulations for incorporating of a regional airline company in Turkey. SHY-6A is the main civil aviation regulation annex, which is consisted by Turkish Civil Aviation Authority (SHGM). This regulation leaflet also includes all application processes, guarantee funds, required directory personnel for incorporation of an airline company. These procedures are mentioned detailed in this study. SHY-6A leaflet would be used as a guidance material, not only for incorporation but also for taking decisions for operations. Regulations related to purchasing of the planes or performed operations by leasing and guarantee funds have differences in between. The case study, regarding to those topics, shall be processed on complete legal basis and this action is followed by examination for incorporation of an airline company. The main and first step that shall be achieved is the determination of boundary conditions. Firstly, appropriate market investigation for investment shall be completed and according to this research, periodically and continuously performed routes would be selected. Regarding to this selection, flight operations, hence the headquarter location, the capacity of passengers on every aircraft, decision of the aircraft and engine types according to and flight distances and runway characteristics. In this study, selection of aircraft is being done as a result of observation of low operating costs, high profitability, and flexibility by cabin configuration. The ATR is selected according to those advantages such as innovation, comfort and environmental care for regional operations in terms of profitability for airlines, impact on environment and passenger comfort for the entire aviation market. Therefore, the determination of maintenance costs for the selected aircrafts, crew and maintenance personnel selection and planning of initial and repetitive trainings would be followed by determination of maintenance and flight costs that would result with a prediction to guarantee a profitable investment. To perform a relative cost calculation for the investment it has to be determined the company operation fields, the number and type of aircrafts, crews, maintenance staff, administrative staff. Thus should be followed by determination of incorporation expenses as a result of determining the cost of installation, the license fees, cost of dry-leasing, cost of facilities and IT systems to be installed, staff salaries and training costs are taken into account for the first detailed cost calculations. Hence, prospect period has been calculated for revealing the incorporation cost of a newly established airline company and in addition to this, direct and indirect costs and operating revenues of three-year period has been mentioned in this study. As a result, the return on equity and current market value of the company is tried to be determined. In addition, all incomes and outcomes of the company, starting from the first incorporation costs, which include administrative personnel salaries, initial facility costs, license fees and paid guarantee fees analyzed. As a result, company profitability and market values have identified. Finally, the calculated values thus have been detailed above, are compared with reference investigations in results and conclusion section. All these calculated values have similar trends with references.As summarizing the effect of study, the results end up with almost current values that give strong evidence for the right assumptions in between the calculations. The percentage of the flight crew salaries in direct operational costs are surprisingly end up with similar values compared historical data and this value is about 15% of direct operational costs. In this study, wet-lease model has chosen for the calculations relevant company operations. The future prospect studies would be derived from all the other models that have defined in operational model section of the study. Furthermore, studies would be continued on all other regions and other civil aviation regulations specified by local authorities. Thus, the differences and similarities in between all these documentations could be compared as upcoming studies from this thesis. According to recent records, positive growth on domestic and inbound tourism has been achieved in Turkey. On the other hand, many promotional and marketing activities that The Ministry of Culture and Tourism have performed had a positive impact on the growth of travel and tourism in Turkey. From all this, it is observed that Turkey has quite a favorable profile for the development of regional air transportation.
Incorporation Of A Regional Airline In Turkey
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: bölgesel havayolu şirketi; shy-6a; bölgesel jet; turboprop; uçak; regional airline; easa; turboprop; jet; aircraft